Cloud Readiness Index 2018 - Shrikanth G (2018)
"Asia-Pacific strengthens its cloud capabilities emerging markets continue to play catch-up. India and China have both made significant progress in driving the regions adoption of cloud-driven technologies, playing central roles in the regions technological development. yet at 12th and 13th positions respectively, they both remain at the bottom of the CRI rankings."
Keywords: Information Technology